Mathematics, Language and Translation - Sarukkai, Sundar (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractThe mathematical discourse is not possible without a fertile use of natural language. Its symbols, first and foremost, refer to natural language terms. Its texts are a combination of symbols, natural language, diagrams and so on. To coherently read these texts is to be involved in the activity of translation. Applied mathematics, as in physics, constantly shifts from one language (and culture) to another and, therefore, is best understood within the ambit of translation studies.